Responses of the English-Language-Teaching Community to the COVID-19 Pandemic - Dr. Jessica Silve; Dr. Lou Desmond (Al-Qanṭara, 2022)
Abstract The global pandemic brought on by the COVID-19 virus has had a profound and disruptive effect on English-language instruction. To prevent the spread of the virus, teachers and students were required to suspend in-person instruction. This resulted in the widespread implementation of synchronous and asynchronous online instruction. Clearly, this period has posed significant challenges for both teachers and students, but it has also provided a rare opportunity to examine the potential benefits of online instruction in English-language education. This study, a systematic thematic review of empirical studies related to English-language teaching and the COVID-19 pandemic, identifies and analyses the most important knowledge generated by the English-language teaching community during the pandemic. It concludes with a discussion of the pandemic's lessons learned and potential areas for future research.